Pengaruh Komunikasi Pemasaran Thrift Shop terhadap Tingkat Konsumsi Fashion di Masa Pandemi - Amirah Shinta Permatasari; Swandhika Rahmadhan; Wildan Julian Firdausy; Heppy Lilaelsa Meidianti (Jurnal Ilmu Komunikasi, 2021)
The era of the COVID-19 pandemic has changed the way people live, from offline to online. This study discusses the effect of thrift shop marketing communications on the level of fashion consumption during the pandemic. The purpose of this study is to determine the level of consumption of a person in shopping, especially Thrift Shop goods. The research method used is a quantitative approach with simple random sampling technique. The results showed that from the analysis of data calculations carried out 53.2% of respondents made the last purchase, then 32.4% had bought from the previous 2 months and 14.4% had bought 1 month earlier, so Ho was accepted while Ha was rejected. It can be concluded that the phenomenon of Thrift Shop products does not affect the consumption pattern of people's fashion products because most of the purchasing trends for Thrift products during the last three months are still passive in purchasing Thrift products on various E-Commerce platforms and social media.